Enhancing Teacher Engagement and Organizational Motivation Through the Interpersonal Communication Strategies of School Principals - Mawaddah Tun’nisa; Nasrul Syakur Chaniago (Journal of Educational Management Research, 2026)
This study aims to explore how the interpersonal communication patterns of school principals contribute to enhancing organizational motivation among teachers. Specifically, it examines the forms of communication employed to address motivational challenges, the current condition of teacher motivation, and the factors influencing principal-teacher interactions. A descriptive qualitative approach with field research was employed, involving interviews, observations, and document analysis with principals, vice-principals, teachers, and education staff as informants. Data were analyzed through data collection, reduction, presentation, and conclusion drawing, while validity was ensured using source, technique, and time triangulation. Findings indicate that principals implement interpersonal communication effectively through a combination of formal and informal channels that are open, dialogical, and supportive, fostering teacher motivation via clear direction, appreciation, active participation, and harmonious working relationships. Key supporting factors include open and egalitarian leadership, a conducive work environment, and a stable organizational climate. These results suggest that principal communication strategies are vital for promoting organizational motivation and cultivating a positive and collaborative school culture.